Effect of Parental Myopia on Change in Refraction in Shanghai Preschoolers: A 1-Year Prospective Study - Ma, Yingyan; Lin, Senlin; Zhu, Jianfeng; Zhao, Rong; Zhang, Bo; Yin, Yao; Shao, Yueqin; He, Xiangui; Xu, Xun; Zou, Haidong (Frontiers in Pediatrics, 2022)
Background To investigate the risk factors for change in refraction and refractive components in preschoolers. Methods Preschool children aged 3–5 years old, from the junior and the middle grades of seven randomly selected kindergartens in Jia Ding District, Shanghai, were followed for 1 year. Cycloplegic autorefraction (1% cyclopentolate) and axial length (AL) were measured at baseline and at 1-year follow-up. Questionnaires about parental myopia and environmental risk factors, such as time of outdoors and near work, were collected. Results A total of 603 right eyes of 603 children were included. Parental myopia was not associated with a change in refraction, but two myopic parents were associated with a longer change in AL (coefficient = 0.153, p = 0.006), after adjusted for baseline spherical refraction, age, gender, change in height, change in weight, and environment risk factors. In the multivariate analyses, boys showed a more myopic refraction shift than girls in 1 year (coefficient = −0.150, p = 0.008) and a quicker AL elongation (coefficient = 0.120, p = 0.008). Time of near work, such as watching television, using computer, reading and writing, and time of outdoor activities, was not associated with a change in refraction or AL. Conclusions In preschool age, environmental risk factors were not strongly associated with the change in refraction or refractive components. Parental myopia influences the refractive development of children continuously from infancy to preschool age, which might be the biological basis of school myopia.